Risk, governance and the experience of care. Issue 6 (29th January 2013) - Hillman, Alexandra; Tadd, Win; Calnan, Sian; Calnan, Michael; Bayer, Antony; Read, Simon
Abstract: Drawing on perspectives from the governmentality literature and the sociology of risk, this article explores the strategies, tools and mechanisms for managing risk in acute hospital trusts in the United Kingdom. The article uses qualitative material from an ethnographic study of four acute hospital trusts undertaken between 2008 and 2010 focusing on the provision of dignified care for older people. Extracts from ethnographic material show how the organisational mechanisms that seek to manage risk shape the ways in which staff interact with and care for patients. The article bridges the gap between the sociological analysis of policy priorities, management strategy and the organisational cultures of the NHS, and the everyday interactions of care provision. In bringing together this ethnographic material with sociological debates on the regulation of healthcare, the article highlights the specific ways in which forms of governance shape how staff care for their patients challenging the possibility of providing dignified care for older people.